The Role of Digital Tools in Biostatistics and Medical Data Analysis in Higher Medical Education (KIUT Publication, 2025)
The goal of this global strategy is to strengthen the healthcare system by applying digital health technologies for consumers, empowering patients, and achieving the vision of health for all through collaboration among healthcare professionals, providers, and the industry.